Selection of Varieties and Hybrids of Squash and Identification of Planting Dates - Fayzullaevich, Durhodjaev Shavkat; Allayorovich, Boltayev Murodbek (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article is given the results of experiment of the Patison cultivation in the climatic conditions of Uzbekistan, planting in different times, growth, development and yield capacity, and the influence of weather. Patison - annual plant belonging to the gourd plant family, usually grows as a shrub, in rare cases it is in the form of a whip. The stem is straight, faceted, rigidly cyst, shortened between the nodes. The length of the crooked stem is 30-60 cm. The product is oval in the form of a plate and a bell, the color is white or dark yellow. It is early maturing variety of the pumpkin family. The period between growth and harvest is 40-50 days. According to the results of the study, we achieved high yields in the cultivation of varieties "Beliy 13" and "Zarkokil".